Growth of rylene diimide crystalline layers on aminoalkyl triethoxysilane-monolayers for organic field effect transistor applications - Geyer, Florian Ludwig; Pun, Andrew; Hanifi, David; Bunz, Uwe H. F.; Liu, Yi (Journal of materials chemistry. C, Materials for optical and electronic devices, 2013)
Macroscopically aligned, crystalline layers are a key requirement for high-performance organic field effect transistors from small molecule organic semiconductors. We investigated the crystallization behavior of n-type semiconducting naphthalene and perylene diimides at the liquid/solid/air interface as a solvent meniscus - evaporation-induced - slowly moved along the surface of a monolayer functionalized Si/SiO2. Amine-terminated, triethoxysilane based functional polar monolayers enforce highly oriented crystallization of the respective rylene diimides at the three-phase border. The electron transporting properties of the resulting crystalline layers of rylene diimides were studied in bottom gate-top electrode field effect transistors, which were shown to be improved up to two orders of magnitude over those of solution casted films. Anisotropic effects expected for crystalline devices were also revealed, which corroborated with the macroscopically oriented crystalline planes observed by polarized optical microscopy.
Gesehen am 04.02.2020